Analytical Models for Determining the Propagation of Rectangular Surface Jets for Fishway Attraction Flow - Wiering, Veronika; Heneka, Patrick; Henning, Martin; Bergmann, Linda (Journal of Coastal and Hydraulic Structures, 2022)
The present paper evaluates suitability of two analytical models to determine the propagation of rectangular surface jets as a tool to design fishway attraction flow. It focuses on rectangular orifices of vertical slot fishways with aspect ratios (width-to-height) for W/H < 1. Both models were rewritten to match boundary conditions for fishways because they were initially derived for horizontal orifices. As the basis for the evaluation, the output of the analytical models to RANS simulations for 12 geometries 1/16 <= W/H <= 4 is compared. Applied analytical equations for half-lengths for cases W/H >= 4 are within 5 % of RANS modeling results for all cases. The location of centerline transition locations from analytical models also agree reasonably well with RANS modeling. The findings support efficient design of optimum attraction flow propagation using simple, rapid analytical approaches.